Botulinum toxin in aesthetic procedures: An integrative literature review (Research, Society and Development, 2023)
Introduction: the use of botulinum toxin has become an increasingly common and widely recognized practice in the area of aesthetics, providing satisfactory results and contributing to the improvement of facial aesthetics. Objectives: to identify in the national and international literature studies on the use of botulinum toxin in aesthetics. Methodology: This is an integrative literature review. Data collection was carried out by searching for scientific papers published in the Virtual Health Library (BVS-BIREME) database in the last ten years and without language restrictions. For the selection of studies, the following descriptors were used: “Botulinum toxin type A” and “Aesthetics”. Results: seven studies were found that responded to the research objective. The studies pointed to the importance of professional training, the need for a solid foundation on the different application techniques, as well as anatomical aspects and possible adverse effects. In addition, the importance of validated protocols on the use of the toxin was highlighted, in order to bring safety to professionals. Final considerations: botulinum toxin is a powerful tool in facial aesthetics, offering satisfactory results in rejuvenation and improvement of appearance. However, it is crucial to highlight the importance of professional training to ensure the safe and effective use of this substance. Application requires in-depth knowledge of facial anatomy, injection techniques and proper dosages. Training ensures safe procedures, minimizing risks of adverse effects. It is noteworthy that the aesthetic benefits go beyond appearance, raising self-esteem and promoting psychological and social well-being.